DROSS DUST PROCESSING - Sedo, Jan (European Scientific Journal, ESJ, 2014)
The paper deals with the processing of dross dust fractions from fluxless rotary furnace to the mentioned products by dry process. It means thatthe procedure of leaching of the soluble components is not used as the lawsalt content from melting process with a salt factor below 0,2 is acceptablylow. The undersize non-smeltable parts are a source of raw materials for thepellets production. Strength and drying of the pellets are provided byexothermic reaction, suitable binders, and combinations of the mixturegranulometry. This paper describes the history of the research anddevelopment of the processing of dross dust fractions in the Confal Inc.,which is currently still developing. Confal, Inc. operates on research anddevelopment program along with Developmental and realization shopof Faculty BERG Kosice. The purpose of the research and developmentprogram is the continual production of dry pellets.